Change in structure between the I=1/2 states in 181 Tl and 177,179Au - Cubiss, James; Barzakh, A. E.; Andreyev, A. N.; Al Monthery, M.; Althubiti, N.; Andel, B.; Antalic, S.; Atanasov, Dinko; Blaum, Klaus; Cocolios, T. E.; Day Goodacre, T.; de Groote, R. P.; et al. (Physics letters, 2018)
The first accurate measurements of the α-decay branching ratio and half-life of the Iπ=1/2+ ground state in 181Tl have been made, along with the first determination of the magnetic moments and I=1/2 spin assignments of the ground states in 177,179Au. The results are discussed within the complementary systematics of the reduced α-decay widths and nuclear g factors of low-lying, Iπ=1/2+ states in the neutron-deficient lead region. The findings shed light on the unexpected hindrance of the 1/2+→1/2+, 181Tl→g177Aug α decay, which is explained by a mixing of π3s1/2 and π2d3/2 configurations in 177Aug, whilst 181Tlg remains a near-pure π3s1/2. This conclusion is inferred from the g factor of 177Aug which has an intermediate value between those of π3s1/2 and π2d3/2 states. A similar mixed configuration is proposed for the Iπ=1/2+ ground state of 179Au. This mixing may provide evidence for triaxial shapes in the ground states in these nuclei.